Supercapacitive properties of carbazole-containing cobalt(ii) phthalocyanines/reduced graphene oxide composites - BUDAK, ÖZLEM; KOCA, ATIF (My University, 2023)
This study aims to compare the effect of substituents (position and number) and reduced graphene oxide on the supercapacitive properties of cobalt(ii) phthalocyanines. For this purpose, three new tetra- and octa-substituted cobalt(ii) phthalocyanines bearing 9H-carbazol-2-yloxy groups on peripheral or non-peripheral positions (1-3) were synthesized. The characterization of the resultant cobalt(ii) phthalocyanines was carried out by applying several spectroscopic approaches. The newly synthesized macromolecules were used for the functionalization of reduced graphene oxide (rGO). The obtained nanocomposites (rGO-(1-3)) were utilized for the modification of Ni foam (NiF) electrodes through a facile one-step electrodeposition strategy performed for electrochemical supercapacitor applications. Simultaneous polymerization of the cobalt phthalocyanines and electrochemically reduction of graphene oxide led to the formation of a fabricating layer on the surface of the NiF electrode. The resulting electropolymerized films were characterized by Raman, Fourier-transform infrared (FT-IR), and Field emission scanning electron microscope (FESEM) spectroscopic techniques as well as electrochemical methods. The prepared electrodes possessed superior electrochemical activities owing to the synergistic effect of the cobalt(ii) phthalocyanines and rGO. All the modified electrodes displayed high supercapacitaive properties and the highest activity was obtained for the NiF/rGO2-1 electrode. The NiF/rGO2-1 electrode exhibited higher specific capacitance (655.2 F g−1 at 0.5 A g−1) than NiF/1 (338.0 F g−1). Additionally, a specific capacitance of 85.2% was obtained for NiF/rGO2-1 electrode after 3000 charge-discharge cycles. As a result, all the prepared metallophthalocyanines-reduced graphene oxide can be considered alternative agents to develop high performance-next-generation energy storage devices.
Keywords: Kimya; İnorganik Kimya; Temel Bilimler; Chemistry; Inorganic Chemistry; Natural Sciences; Temel Bilimler (SCI); KİMYA, İNORGANİK VE NÜKLEER; Natural Sciences (SCI); CHEMISTRY; CHEMISTRY, INORGANIC & NUCLEAR; İnorganik kimya; Fizik Bilimleri; Physical Sciences